Evaluation of Different Varieties of Pea under Agro-Climatic Conditions of Gilgit-Baltistan - Muhammad Din; Faizullah Khan; Abdul Karim; Tajuddin; Saifullah (Advances in Food Technology and Nutrition Sciences, 2019)
Introduction Pea (Pisumsativum L) is an important crop which is used both as food and fodder purpose. Peas are highly nutritious; pea is used both as vegetable and pulse. Materials and Methods Five pea varieties were evaluated for their performance at mountain agricultural research centre (MARC), Juglote, Gilgit during 2017. The varieties are climax, pasan, rondo, meteor and green feast. Results Differences among plant heights of pea varieties were significant with maximum plant height of 85.25 cm noted in plots of variety climax, while the minimum plant height of 45.75 cm was recorded in plots of variety rondo. Number of branches per plant of the different varieties ranged significantly from a minimum of 2.15 (green feast)to a maximum of 4.00 (meteor). Average number of pods per plant varied significantly between 10.84 and 13.71.Maximum pods per plant were found from variety climax (13.71) followed by green feast (13.58). Maximum pod length of 7.900 cm was recorded for variety Rondo, followed by variety green feast with pod length of 5.800 cm, while the minimum of 5.220 cm was recorded for the verity meteor. Maximum pod weight 26.29 kg per plot was obtained from variety climax, followed by 21.75 kg per plot from variety green feast, the minimum pods weight was recorded for variety meteor 16.20 kg per plot. Difference in pods yield of the five varieties were significant, with a maximum pods yield of 3585 kg per hectare recorded for variety climax, followed by 3545 kg per hectare for cultivar green feast and minimum of 2491 kg per hectare noted for variety rondo. Conclusion Therefore, variety climax being the highest yielder can be recommended to the pea growers of Gilgit-Baltistan for commercial cultivation.